Management of Non-Traumatic Acute Abdominal Pain in Elderly Patients - Atshan, Dr. Fadhil Ghadhban; Assi, Prof. Dr. Ali Nayyef (American Journal of Biomedicine and Pharmacy, 2024)
OBJECTIVE. The aim of this study is to evaluate the effects of physiological changes in elderly patients in management of non-traumatic acute abdominal pain. MATERIALS AND METHODS. After ethical approval, in the study, 50 patients were included and they were admitted in ED of Al- Hussein teaching hospital in Al-Nasiriya city South of Iraq. Patients age was range between 65 to 80s years, the chief complaint was abdominal pain and they present to hospital between April 2017 - August 2017. The patients were divided into two subgroups, group A (65–74 years) and B (> 75 years). Inclusion criteria include non-traumatic abdominal pain patients older than 65 years. Exclusion criteria: patients less than 65 years old and those with traumatic abdominal pain. RESULTS. From 50 old age patients were admitted to the ED the total number and percentage of patient underwent surgery were 18 patients (36%)15 patients from group A (old age patients) (37.5%) while 3 elderly patients (30 %) from group B. The operations that were done in group A 2 patients for perforated peptic ulcer, 4 appendectomies, 4 cholecystectomies, 3 for surgical management of intestinal obstruction due to tumor and 5 operations for management of obstructed hernia, while other patients were treated conservatively. The percentage of non –malignant intestinal obstruction was 83.3% (18 patients). CONCLUSION. Physiological changes related to aging process with comorbidities have adverse effects in clinical findings and making difficultly or delay in diagnosis of acute abdominal pain in elderly patient, so it is important to strictly adherence to guide lines in management of acute abdominal pain in geriatric patients.